The systemic inflammation indexes predict all-cause mortality in peritoneal dialysis patients - Yan Yang; Yuanyuan Xu; Shusu Liu; Peiyu Lu; Hua Zhou; Min Yang (Renal Failure)
Background Chronic inflammation is a common complication in peritoneal dialysis (PD) patients. The aim of this study is to investigate the capacity of aggregate index of systemic inflammation (AISI), systemic immune-inflammation index (SII), and systemic inflammation response index (SIRI) to predict all-cause mortality in PD patients.Methods This was a single-center retrospective study. The optimal cutoff values were identified by receiver operating characteristic (ROC) curve analysis. The area under the curve (AUC) was calculated to evaluate the predictive ability of these indexes. The Kaplan–Meier curves and log-rank test were performed to estimate cumulative survival rate. Cox proportional hazards regression analyses were conducted to determine the independent prognostic power of inflammation indexes.Results A total of 369 incident PD patients were involved. During a median follow-up period of 32.83 months, 65 patients (24.2%) died. The ROC analysis indicated the largest value of AUC was obtained for SII (AUC = 0.644, 95% CI = 0.573–0.715, p < .001), followed in order by AISI (AUC = 0.617, 95% CI = 0.541–0.693, p = .003), and SIRI (AUC = 0.612, 95% CI = 0.535–0.688, p  = .004). The Kaplan–Meier survival curves revealed significantly lower survival rate with higher AISI (p  = .001), higher SSI (p  = .001), and higher SIRI (p  = .003). Even after adjustment for the confounding factors, higher AISI [hazard ratio (HR)=2.508, 95% confidence intervals (CI)=1.505–4.179, p < .001), SII (HR = 3.477, 95% CI = 1.785–6.775, p < .001), and SIRI (HR = 1.711, 95% CI = 1.012–2.895, p  = .045) remained as independent predictors of all-cause mortality.Conclusions The higher AISI, SII, and SIRI were independent indicators of all-cause mortality in PD patients. Furthermore, they could provide comparable predictive value and assist clinicians to ameliorate PD management.